Politeness Strategies and Politeness Principles In The Dialogues Of The Character Afaf in the Film From the Ashes by Khalid Fahad (A Pragmatic Study) - Aida Zakiyah Munawaroh; Muhammad Nurhasan; Yadi Mardiansyah (Al-Irfan : Journal of Arabic Literature and Islamic Studies, 2026)
This study aims to identify and describe the politeness strategies proposed by Brown and Levinson and the politeness principles proposed by Geoffrey Leech used by the character Afaf in the film From The Ashes directed by Khalid Fahad. This research employs a qualitative approach using a descriptive-analytical method. The research data consist of Afaf's utterances, collected through the non-participatory observation method and note-taking technique. The data were analyzed using the pragmatic identity method. The findings reveal 83 data items, consisting of 39 politeness strategy data, dominated by the bald-on record strategy with 32 occurrences, and 44 politeness principle data, dominated by violations of the tact maxim with 26 occurrences. The analysis also indicates that the bald-on record strategy may be associated with either maxim compliance or maxim violation, depending on the context of the utterance. Meanwhile, positive politeness is more frequently associated with maxim compliance, whereas the off-record strategy tends to be associated with maxim violations. Based on these findings, it can be concluded that Afaf predominantly employs the bald-on record strategy and tends to violate politeness principles more frequently in her interactions.